Interactive Multimedia with a Scientific Approach to Craft Subjects, Material for Processing Livestock and Fishery Products - Manissa, Athalla; Putu Parmiti, Desak; Sudarma, I Komang (Universitas Pendidikan Ganesha, 2023)
Learning in Crafts subjects is still teacher-centered with the lecture method, resulting in students needing to be more active and able to learn independently. With such learning, student learning outcomes continue to decline rather than show improvement. This research aims to develop interactive multimedia with a scientific approach to craft subjects. The research used the ADDIE model with research subjects, namely content experts, design experts, and learning media experts, three individual trial students, and six small group trial students. The data collection methods used were questionnaires, pre-tests, and post-tests. The research results were validated by media experts categorized as very good qualifications, media design experts with very good qualifications, content experts with very good qualifications. The validation results through individual trials have very good qualifications and small group trials have very good qualifications. This interactive multimedia was declared effective because it was seen from the average results of the pre-test and post-test. Based on the results of the effectiveness test of interactive multimedia crafts with a scientific approach, there are significant differences in student learning outcomes before and after using interactive multimedia with a scientific approach.